Fibers for Technical Textiles - Ahmad, Sheraz; Rasheed, Abher; Nawab, Yasir; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This book discusses the properties of fibres used in manufacturing technical textiles, highlighting the importance of material selection in terms of cost, end-user requirements and properties. It also discusses the classification of technical textiles, and describes the details of each category, such as the properties, applications, advantages and drawbacks. As such, it is a valuable resource for all those interested in advanced textiles.
Chapter 1 - Introduction -- Chapter 2 - Fibers for Technical Textiles -- Chapter 3 - Classification of Technical Textiles -- Chapter 4 - Fibers for Protective Textiles -- Chapter 5 - Fibers for Sports Textiles -- Chapter 6 - Fibers for Automobiles -- Chapter 7 - Fibers for Geotextiles -- Chapter 8 - Fibers for Agro Textiles -- Chapter 9 - Fibers for Medical Textiles -- Chapter 10 - Fibers for Other Technical Textile applications.
Keywords: Ceramics; Glass; Composites (Materials).; Composite materials; Engineering$1 (BMaterials.s; Ceramics, Glass, Composites, Natural Materials; Materials Engineering